Dinamika Sosial-Ekonomi Nelayan Tanjung Benoa dalam Perkembangan Wisata Bahari di Bali Selatan pada Tahun 1993 – 2022 - Natania, Ida Ayu Made Keshya; Anak Agung Inten Asmariati; Putu Dyah Pradnya Paramitha (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This research is entitled Socio-Economic Dynamics of Tanjung Benoa Fishermen in the Development of Marine Tourism in South Bali, 1993–2022. The study aims to examine the socio-economic changes of fishing communities, the factors driving these changes, and the implications of marine tourism development on the lives of the Tanjung Benoa community. This research employs the historical research method, including heuristics, source criticism, interpretation, and historiography. Data were collected through interviews, observations, and literature studies of written sources and archives related to the development of Tanjung Benoa. The results show that the designation of Tanjung Benoa as a marine tourism area in 1993 became the starting point for the socio-economic transformation of coastal communities. The development of marine tourism created new economic opportunities, leading many fishermen to shift their professions to tourism-related occupations such as watersport operators, tour guides, and other service businesses, which contributed to increased community income. However, these changes also led to shifts in social structure, the emergence of new economic classes, and unequal access to economic resources. In addition, there were changes in cultural values and community perspectives toward the sea, from a living space to a commercial economic space. Nevertheless, the Tanjung Benoa community continues to maintain cultural values and local traditions as the identity of coastal society. Overall, the development of marine tourism in Tanjung Benoa reflects dynamic socio-economic transformation influenced by government policies, tourism investment, and the adaptability of local communities in facing modernization and globalization.